Designing an Effective Learning Environment for Language Learning During the Covid-19 Pandemic - Betoncu, Olkan; Faslı, Funda G.; Ozdamli, Fezile (Frontiers in psychology, 2021)
The rapid development in IT in the twenty-first century have along with the COVID-19 pandemic have had effects on the field of education, with the need to use technology for educational purposes arising. Mobile phones, which hold a more important place than computers, also became a part of education. In today's world, it is possible to access educational content without any limitation of time and space. Individuals who desire to learn a new language but cannot do so due to financial difficulties or free time have moved toward mobile learning methods. “YIT101” is a mobile application designed to teach Turkish as a foreign language independent from time and location and targets basic Turkish A1 level course content. This application enables users to access information when needed and to learn Turkish as a foreign language outside the classroom environment independent from a formal instructor, allowing them to save time.